2007
DOI: 10.1063/1.2430908
|View full text |Cite
|
Sign up to set email alerts
|

Infrared characterization of hafnium oxide grown by atomic layer deposition using ozone as the oxygen precursor

Abstract: Hf O 2 growth on H-terminated Si surfaces by atomic layer deposition (ALD) is studied with in situ Fourier transform infrared spectroscopy and ex situ Rutherford backscattering, using tetrakis-(ethyl-methyl-amino) hafnium and ozone as the hafnium and oxygen precursors, and compared to water-vapor-based ALD growth. The reaction pathways are different for the two oxygen precursors, leading to a lower growth rate for ozone (∼0.05nm∕cycle) than for water-based growth and to incorporation of different impurities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…In addition, O 3 can be purged more easily from the reactor chamber than H 2 O, thus enhancing the throughput of wafers. [34][35][36] This study also includes analysis of the ALD-produced NiO film properties, and a comparison with films deposited by CVD using the same Ni(dmamb) 2 precursor. [37] 2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, O 3 can be purged more easily from the reactor chamber than H 2 O, thus enhancing the throughput of wafers. [34][35][36] This study also includes analysis of the ALD-produced NiO film properties, and a comparison with films deposited by CVD using the same Ni(dmamb) 2 precursor. [37] 2.…”
Section: Introductionmentioning
confidence: 99%
“…10 Such substantial oxidation resulting in the formation of higher oxidation states would be expected to impact III-V transistor device characteristics negatively. 20 In contrast, recent studies suggest using an unidentified "organometallic" Zr precursor in conjunction with ozone as a promising approach for gate dielectrics on In 0.53 Ga 0.47 As.…”
mentioning
confidence: 99%
“…Due to the associated sticking coefficients of O 3 and H 2 O, it is more facile to evacuate O 3 from the reactor during the purge relative to H 2 O, thus leaving no residual oxygen to decompose the tri-methyl aluminum ͑TMA͒ into Al 2 O 3 before it reaches the surface, reducing the possibility of forming O-H bonds in the film. 10 Sulfur-doped ͑4 ϫ 10 17 cm −3 ͒ In 0.53 Ga 0.47 As ͑ϳ7.6 cm diameter͒ grown by metallorganic vapor phase epitaxy on heavily doped ͑S ϳ 4 ϫ 10 18 cm −3 ͒ InP͑100͒ wafers were used in this study. The Al 2 O 3 thin films were deposited by ALD on ammonium-sulfidepassivated ͓10% ͑NH 4 ͒ 2 S for 20 min at ϳ20°C͔ surfaces ͑ϳ1 ϫ 1 cm 2 ͒ cleaved from the wafer, which initially underwent a degrease process of 1 min each in acetone, methanol, and isopropanol and blown dry with nitrogen.…”
mentioning
confidence: 99%
“…These may have been associated with the SiO 2 network disruption occurred upon forming the pseudobinary alloy with HfO 2. It was shown that even at the small HfO 2 content; the SiO 2 network undergoes appreciable disruption [3,4,5,[7][8][9][10][11]. It should be emphasized that the SiO 2 network disruption resulted in the shift of TO band from ω=810 cm -1 to ω=750 см -1 (see Fig.…”
Section: Resultsmentioning
confidence: 94%